(untitled) (New York, 2002)
Highlighting the role of dietary fats in foods, human health, and disease, this book offers comprehensive presentations of lipids in food. Furnishing a solid background in lipid nomenclature and classification, it contains over 3600 bibliographic citations for more in-depth exploration of specific topics and over 530 illustrations, tables, and equations to help clarify study. With contributions of more than 40 internationally renowned experts, the book covers conjugated linoleic acids in health, and food applications of lipids.
Keywords: Chất béo,Lipids.,Lipids; Công nghệ sinh học,Biotechnology